Assessing the Effects of Cancer Diagnosis and Coping Strategies on Patients in Vhembe District Hospitals, Limpopo Province - Dorah Ursula Ramathuba; Takalani Friddah Rafundisani; Maria Sonto Maputle (Nursing Reports, 2025)
Background: Unlike other chronic diseases, cancer patients undergo different types of treatments that affect their well-being, and as a result, they tend to have different experiences from those of other chronic disease sufferers. The purpose of this study was to assess the effects of cancer diagnosis and coping strategies on patients in Vhembe District hospitals in Limpopo Province. Methodology: The study design used was a quantitative descriptive cross-sectional survey. The target population included patients in the Vhembe District of Limpopo who had started treatment within the last year. Probability-stratified sampling was used to sample 207 patients from seven selected hospitals in Vhembe District. A self-administered questionnaire was used to collect data, and the data were analyzed using a software package for descriptive statistics (SPSS version 23). Tables were used to display the results visually, and chi-square tests were used to compare the variables. Ethical principles were considered for the participants’ privacy, anonymity, and informed consent. Findings: The findings revealed that the majority of patients 185 (89.4%) experienced a sense of psychosocial distress such as emotional pain; 142 (68.6%) participants experienced hopelessness and despair, 127 (61.3%) resorted to substance use, 160 (77.3%) did not have a positive attitude towards seeking the medical and other support resources available, only a minority resorted to spirituality, and 121 (63.2%) indicated seeking further clarity about the disease. The study recommends supporting cancer patients and their families through the cancer journey. Contributions: Clinicians should provide psychosocial support interventions to enhance mental health and quality of life in cancer patients, and decentralize oncology services by including primary care professionals in delivering chronic illness disease management strategies.